2016
DOI: 10.1103/physrevlett.116.193001
|View full text |Cite
|
Sign up to set email alerts
|

Steering Proton Migration in Hydrocarbons Using Intense Few-Cycle Laser Fields

Abstract: Proton migration is a ubiquitous process in chemical reactions related to biology, combustion, and catalysis. Thus, the ability to manipulate the movement of nuclei with tailored light within a hydrocarbon molecule holds promise for far-reaching applications. Here, we demonstrate the steering of hydrogen migration in simple hydrocarbons, namely, acetylene and allene, using waveform-controlled, few-cycle laser pulses. The rearrangement dynamics is monitored using coincident 3D momentum imaging spectroscopy and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 36 publications
1
74
0
Order By: Relevance
“…[32] for the deprotonation of acetylene and in Ref. [34] for the isomerization of acetylene. Briefly, the wave packet possesses a preferential propagation direction, which is determined by the CEP.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] for the deprotonation of acetylene and in Ref. [34] for the isomerization of acetylene. Briefly, the wave packet possesses a preferential propagation direction, which is determined by the CEP.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[30][31][32][33][34][35]). CEP effects in the deprotonation of acetylene, induced by few-cycle laser pulses, have attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Upon ionization, the molecular structure and the corresponding chemical properties can change drastically, e.g., due to proton migration, 1 dissociation, 2 or even selective bond-breaking 3 . To temporally resolve the resultant vibrational motion, Coulomb explosion imaging (CEI) can be applied to reveal the underlying nuclear dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that H 3 + can be emitted from hydrocarbon molecular dication prepared by electron impact ionization 2 , by extreme ultraviolet photoionization 3 , and by irradiation of intense femtosecond laser pulses [4][5][6] . The formation of H 3 + from allene [7][8][9] and the formation of HD 2 + from CD 3 OH 10 showed that migration of hydrogen atoms can proceed in the formation of H 3 + . Recently, we interpreted the mechanism of H 3 + formation from dication of methanol theoretically as a unimolecular decomposition process in which a long-lived neutral moiety of H 2 , formed within a dication molecule, abstracts a proton in the other moiety having the charge of +2 11 .…”
mentioning
confidence: 99%